1996
DOI: 10.1055/s-0038-1650393
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive Bioimmunoassay for Thrombin-cleaved Two-chain Urokinase-type Plasminogen Activator in Human Body Fluids

Abstract: SummaryThrombin cleaves single-chain urokinase-type plasminogen activator (scu-PA) into a two-chain form (tcu-PA/T), which is virtually inactive in plasminogen activator assays. Little is known about the physiological importance of tcu-PA/T. To examine the occurrence of tcu-PA/T in vivo, we developed a sensitive and specific bioimmunoassay (BIA) for the assessment of tcu-PA/T in human body fluids. In this BIA, urokinase antigen was immuno-immobilized in microtiter plates and treated with cathepsin C, a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…4C) supports this hypothesis. It has previously been shown that thrombin can cleave scuPA both in purified system [13] and in vivo: in synovial and intravascular spaces [18]. Thrombin cleaved scuPA could be activated and reliably detected in the complex protein mixtures, including biological fluids, as demonstrated in these studies.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…4C) supports this hypothesis. It has previously been shown that thrombin can cleave scuPA both in purified system [13] and in vivo: in synovial and intravascular spaces [18]. Thrombin cleaved scuPA could be activated and reliably detected in the complex protein mixtures, including biological fluids, as demonstrated in these studies.…”
Section: Discussionsupporting
confidence: 57%
“…While cleavage of scuPA is a putative mechanism by which fibrin is protected from early fibrinolysis, the role of this pathway in the regulation of intrapleural fibrinolysis has not been investigated. Thrombin-cleaved uPA has previously been detected in plasma of patients with sepsis [18] and in synovial fluids of patients with rheumatoid arthritis [18], leading us to infer that thrombin-TM-mediated cleavage of scuPA contributes to intrapleural regulation of fibrinolysis during evolving pleurodesis or other pleural diseases. We also inferred that this mechanism may be involved in cleavage of exogenous scuPA, which prevents intrapleural loculations and lung trapping induced by tetracycline and is being evaluated as a candidate for future clinical use [16].…”
mentioning
confidence: 99%
“…The inactivation of scu-PA has been postulated as a mechanism for protecting a fresh blood clot from early fibrinolysis [3,9]. The inactivation does indeed take place in vivo, as we have demonstrated the presence of tcu-PA/T in human body fluids under pathological conditions that involve the production of large amounts of thrombin [10][11][12].Thrombomodulin accelerates the inactivation of scu-PA by thrombin, both in a purified system and in a plasma milieu [13][14][15]. In addition, it has been shown that endogenous thrombomodulin enhances the inactivation of scu-PA by thrombin in a perfused rabbit heart model, suggesting that this potentiating effect is of significance in vivo [14].…”
supporting
confidence: 54%
“…Previous studies (6)(7)(8)(9) have demonstrated rapid increases in circulating PA levels, as well as increased pulmonary concentrations of uPA after endotoxemia or bacterial infections. These studies document a close temporal relationship between the development of LPS-induced ALI and uPA expression.…”
mentioning
confidence: 97%